Efficiency of Protein Use and Performance of Broiler Chickens Fed Corncob Fermented with EM4 (Effective Microorganisms 4) - Nelwida, Nelwida; Ramadhan, Syahru; Berliana, Berliana; Handoko, Heru; Nurhayati, Nurhayati (Faculty of Agriculture, 2025)
This study aimed to evaluate the use of fermented corncob flour as a substitute for rice bran in broiler chicken rations and its effects on protein efficiency ratio and broiler performance. Conducted at the Farm and Laboratory of the Faculty of Animal Science, University of Jambi, the study tested four treatments on 200 broiler chicks using a Completely Randomized Design (CRD) with five replications. The treatments included 0%, 4%, 8%, and 12% fermented corncob flour as a substitute for rice bran. Key variables observed were feed intake, body weight gain, feed conversion ratio, and protein efficiency ratio. Results indicated that the inclusion of fermented corncob flour significantly (P0.05) improved feed intake, protein intake, protein efficiency ratio, and feed conversion ratio, with no significant impact (P0.05) on body weight gain up to a 12% inclusion level. The optimal feed conversion was observed at the 8% substitution level. In conclusion, corncob flour fermented with EM4 can replace up to 12% of rice bran in broiler rations without negatively affecting performance, providing a viable alternative for poultry feed formulation.